Experiences Enhancing Climate Responsive Agriculture in the Caribbean - Coipel, Kent (Inter-American Institute for Cooperation on Agriculture (IICA), 2023)
Guest speakers: Mr. Kent Coipel, Technical Specialist, Inter-American Institute for Cooperation on Agriculture (IICA) - Dominica, Mr. Laurenzo Tirtopawiro, Technical Specialist, Inter-American Institute for Cooperation on Agriculture (IICA) - Suriname, Mr. Willie Chan, Technical Coordinator, Inter-American Institute for Cooperation on Agriculture (IICA) - Belize